Optimizing food-assistance programs: Food assistance improves child growth in Burundi - Leroy, Jef L.; Olney, Deanna K.; Ruel, Marie T.; Brown, Tracy (International Food Policy Research Institute, 2018)
Food-assisted maternal and child health and nutrition (FA-MCHN) programs have long been used to address hunger and hunger-related problems. Traditionally, such programs targeted families with underweight children younger than five. But a landmark IFPRI study in Haiti showed that preventive interventions—those that target all mothers during pregnancy and the first 6 months of lactation as well as children between 6 and 24 months old (the first 1,000 days)—are more effective than traditional recuperative interventions.